P5 Activity Based on Banyumasan Local Wisdom at the PAUD Institution Sub Topic I Love Banyumas Culture - Mukti Amini; Novan Ardy Wiyani; Murni (Universitas Pendidikan Ganesha, 2025)
Some teachers still face difficulties implementing local wisdom–based P5 due to limitations in designing culturally based activities. Therefore, this study aims to describe, analyze, and implement a local wisdom–based P5 activity design in early childhood education institutions. This research uses qualitative research methods with the type of applied research. Data were collected by interview, observation and documentation techniques. The data that has been collected is then analyzed using the Miles and Huberman model data analysis techniques. This research is the result of the implementation of the first stage of applied research, where the research is limited to the application of P5 activity design based on the local wisdom of the Banyumasan community on the sub-topic